ELECTROREMEDIATION OF ZN(II) CONTAMINATED SOFT BANGKOK CLAY WITH CATHODE DEPOLARIZATION TECHNIQUE - P. Asavadorndeja; K. E. Roehl; U. Glawe; L. Sthapit (Lowland Technology International, 2005)
Four electrokinetic experiments were performed to examine the application of electrokinetic remediation to remove heavy metals from the soft Bangkok clay. The experiments were carried out by applying a direct-current electric field of 20 V through the soil loaded with Zn(II) at the level of 1,000 mg per kg for 3 and 7 days. In addition, the cathode depolarization technique, in which hydroxide ions generated from electrolysis reactions are eliminated by flushing acidic solution into a cathode reservoir, was introduced to improve the efficiency of electrokinetic remediation. The experiment results showed that only electrokinetic remediation was able to remove 82 percent of the contaminants in a period of one week. During this period, the combination of electrokinetic remediation with the cathode depolarization technique has raised the removal efficiency after 7 days of the treatment by 15 percent while the energy expenditure was slightly increased from 273 kWh per m3 to 301 kWh per m 3 . Therefore, the application of electrokinetic remediation with the cathode depolarization technique can be considered as an efficient ground remediation method for the soft Bangkok clay.